Pendampingan Pemanfaatan Nasi Sisa Sebagai Pakan Ternak di Pondok Pesantren Nurul Qur’an Pakunden Ponorogo - Choirul Anam; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This assistance aims to process rice that is no longer used in Islamic boarding schools as food for livestock that is safe, has sufficient nutrition, and does not damage the environment. Leftover rice is a type of food waste that is very large in Islamic boarding schools, so if not managed properly, it can cause waste and pollution problems. With this research, it is hoped that it can add insight into the proper processing of leftover rice so that it can be reused as animal feed. In addition, this research also aims to reduce expenses in buying animal feed, increase the use of resources more efficiently, and help students understand the importance of managing food waste in a useful way. Research on the use of leftover rice as food for livestock at the Nurul Qur'an Islamic Boarding School in Pakunden Ponorogo uses the ABCD (Asset Based Community-driven Development) approach. This approach was chosen because it emphasizes the recognition and utilization of the potential and assets in the boarding school, so that it can be used optimally to improve food independence and environmental management in Islamic boarding schools.